Monoacylglycerol lipase inhibitor JJKK048 ameliorates ABCG2 transporter-mediated regorafenib resistance induced by hypoxia in triple negative breast cancer cells - Puris, Elena; Petralla, Sabrina; Auriola, Seppo; Kidron, Heidi; Fricker, Gert; Gynther, Mikko (Journal of pharmaceutical sciences, 2023)
Triple negative breast cancer (TNBC) is among the most aggressive and deadly cancer subtypes. Intra-tumoral hypoxia is associated with aggressiveness and drug resistance in TNBC. One of the underlying mechanisms of hypoxia-induced drug resistance is the elevated expression of efflux transporters such as breast cancer resistant protein (ABCG2). In the present study, we investigated the possibility of ameliorating ABCG2-mediated drug resistance in hypoxic TNBC cells by monoacylglycerol lipase (MAGL) inhibition and the consequent downregulation of ABCG2 expression. The effect of MAGL inhibition on ABCG2 expression, function, and efficacy of regorafenib, an ABCG2 substrate was investigated in cobalt dichloride (CoCl2) induced pseudohypoxic TNBC (MDA-MB-231) cells, using quantitative targeted absolute proteomics, qRT-PCR, anti-cancer drug accumulation in the cells, cell invasiveness and resazurin-based cell viability assays. Our results showed that hypoxia-induced ABCG2 expression led to low regorafenib intracellular concentrations, reduced the anti-invasiveness efficacy, and elevated half maximal inhibitory concentration (IC50) of regorafenib in vitro MDA-MB-231 cells. MAGL inhibitor, JJKK048, reduced ABCG2 expression, increased regorafenib cell accumulation, which led to higher regorafenib efficacy. In conclusion, hypoxia-induced regorafenib resistance due to ABCG2 over-expression in TNBC cells can be ameliorated by MAGL inhibition.